Silver/dioxide titanium nanocomposites as biocidal treatments on limestones - Becerra Luna, Javier; Zaderenko Partida, Ana Paula; Ortiz Calderón, Pilar (Ge-conservacion, 2017)
Biodegradation of stones is a common and undesirable alteration in historical buildings. Restorers have been using different treatments, especially chemical methods, to prevent biodeterioration. These treatments often have disadvantages such as low long-term effectiveness, high toxicity on human health and the environment and/or physicochemical incompatibility with the original stone (chromatic alteration or chemical degradation).In this research, different biocidal treatments based on silver and titanium dioxide nanocomposites have been tested on limestones from Utrera’s quarry (Seville, Spain), a stone employed in historical buildings in the south of Spain. Two AgNPs syntheses have been studied; the principal difference between them was the use of trisodium citrate as stabilizer.Optimum nanocomposite composition and dosage to minimize chromatic alteration after application of treatments without cut down the biocide effectiveness have been set up. Treatments based on silver-titanium dioxide (Ag/TiO2) nanocomposites stabilized with citrate have been able to keep clean the limestone due to the biopatina formation reduction and the surface color change has been below 10%.